Review of Advanced Drug Trials Focusing on the Reduction of Brain Beta-Amyloid to Prevent and Treat Dementia - Decourt B; Noorda K; Noorda K; Shi J; Sabbagh MN (Dove Medical Press, 2022)
Boris Decourt,1 Keith Noorda,2 Kevin Noorda,2 Jiong Shi,1 Marwan N Sabbagh3 1Cleveland Clinic Lou Ruvo Center for Brain Health, Las Vegas, NV, USA; 2UNLV School of Medicine, Las Vegas, NV, USA; 3Alzheimer's and Memory Disorders Division, Department of Neurology, Barrow Neurological Institute, St. Joseph's Hospital and Medical Center, Phoenix, AZ, USACorrespondence: Marwan N Sabbagh, C/O Neuroscience Publications, Barrow Neurological Institute, St. Joseph's Hospital and Medical Center, 350 W. Thomas Road, Phoenix, AZ, 85013, USA, Tel +1 602.406.3593, Fax +1 602.406.4104, Email Neuropub@barrowneuro.orgAbstract: Alzheimer disease (AD) is the most common neurodegenerative disease and typically affects patients older than age 65. Around this age, the number of neurons begins to gradually decrease in healthy brains, but brains of patients with AD show a marked increase in neuron death, often resulting in a significant loss of cognitive abilities. Cognitive skills affected include information retention, recognition capabilities, and language skills. At present, AD can be definitively diagnosed only through postmortem brain biopsies via the detection of extracellular amyloid beta (Aβ) plaques and intracellular hyperphosphorylated tau neurofibrillary tangles. Because the levels of both Aβ plaques and tau tangles are increased, these 2 proteins are thought to be related to disease progression. Although relatively little is known about the cause of AD and its exact pathobiological development, many forms of treatment have been investigated to determine an effective method for managing AD symptoms by targeting Aβ. These treatments include but are not limited to using small molecules to alter the interactions of Aβ monomers, reducing hyperactivation of neuronal circuits altering Aβ's molecular pathway of synthesis, improving degradation of Aβ, employing passive immunity approaches, and stimulating patients' active immunity to target Aβ. This review summarizes the current therapeutic interventions in Phase II/III of clinical development or higher that are capable of reducing abnormal brain Aβ levels to determine which treatments show the greatest likelihood of clinical efficacy. We conclude that, in the near future, the most promising therapeutic interventions for brain Aβ pathology will likely be passive immunotherapies, with aducanumab and donanemab leading the way, and that these drugs may be combined with antidepressants and acetylcholine esterase inhibitors, which can modulate Aβ synthesis.Keywords: Alzheimer disease, amyloid plaques, clinical trials, immunotherapy, small-molecule drugs